The relationship between health literacy levels and genital hygiene behaviors in female university students - Sağlık, Cavide; Istek, Zekiye; Demirbaş, Ayşegül; Bozkurt, Feyza Demir; Çiçek Gümüş, Ecem (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This study investigates the correlation between health literacy levels and genital hygiene behaviors among female university students. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and method. A descriptive-correlational study was conducted with 348 female students who voluntarily participated. Data were collected through an online survey comprising participant information forms, the Health Literacy Scale, and the Genital Hygiene Behaviors Scale. Statistical analyses, including descriptive statistics, chi-square test for categorical data, and correlation analyses, were performed using SPSS version 26.0. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The mean age of the participants was 21.92±2.51 years. The average scores on the Health Literacy Scale and Genital Hygiene Behaviors Scale were 106.0±17.9 and 86.73±10.13, respectively. Significant differences were observed in genital hygiene behavior scores concerning participants’ field of study and bathing habits. Furthermore, a moderately significant positive correlation was found between women’s health literacy scores and genital hygiene behavior scores. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The study reveals a positive association between high health literacy levels and adequate genital hygiene behaviors among women. As women’s health literacy improves, their genital hygiene behaviors also enhance positively. Access to reliable health information resources is crucial to ensure accurate knowledge acquisition regarding genital hygiene practices.